FLQ: histoire d'un mouvement clandestin - Fournier, Louis (Lanctôt, 1998)
Keywords: Front de Libération du Québec

Working-Class Experience: Rethinking the History of Canadian Labour, 1800-1991 - Palmer, Bryan D. (McClelland & Stewart, 1992)
Keywords: Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail